Polypropylene/clay nanocomposites produced by shear controlled orientation in injection moulding : deformation and fracture properties - Costantino, Alejandra (2013)
The effect of distinct morphologies induced by shear controlled orientation in injection moulding (SCORIM) in the mechanical and fracture performance of polypropylene (PP) and PP/nanoclay mouldings is examined in this work. The effect of high shear conditions applied during processing was assessed. Samples exhibited a range of fracture stability ranging from a modest non-linearity to a quasi-stable regime depending on material type and injection conditions. Neat PP showed non-linear brittle behaviour while nanocomposites exhibited quasi-stable behaviour induced by the large deformation capability of the skin layer. Despite the fracture initiating at practically the same loading levels, the propagation energy varied with processing conditions and nanoclay content. The reduction of the core layer achieved by the SCORIM processing along with the differences between the skin and core favoured by the presence of nanoclay are responsible for the toughening of the SCORIM PP/nanoclay thick mouldings.